Transformation of University Structure in the Aspect of Participation in the Program of Strategic Academic Leadership ‘Priority-2030’ - D. A. Shtykhno; М. N. Kulapov; V. V. Maslennikov; I. A. Kalinina; P. A. Karasev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies an acute issue of university development, in particular the Russian Plekhanov University of Economics, in the context of participation in the contest of universities claiming leadership in working out new academic knowledge, technologies and innovation to be introduced in Russian economy and social sphere under the program of strategic academic leadership ‘Priority 2030’. Restructuring of the current organizational structure of governing educational and academic work acts as a fundamental trend providing implementation of the new strategic program of university development meeting the principles of ‘Priority-2030‘. After a long period of splitting education and science by vertical lines of the predominant linear-functional model, today restructuring implies their integration on the basis of a new strategic unit, i. e. higher school. Concrete advantages of higher school as a new strong point in the system of university governance were demonstrated in comparison with faculties and chairs and hyper-faculties or departments in other universities. A project mechanism of education program management was put forward, which leans on its academic leader. The authors formulated the algorithm of building the academic and educational potential of university and developed a principle scheme of the university educational and academic platform organization, illustrated by the subject field ‘Economic and Management’.